Terrorism Induced Cross-Market Transmission of Shocks: A Case Study Using Intraday Data - Christos Kollias; Stephanos Papadamou; Costas Siriopoulos (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Terrorist incidents exert a negative, albeit generally short-lived, impact on markets and equity returns. Given the integration of global financial markets, mega-terrorist events also have a high contagion potential with their shock waves being transmitted across countries and markets. This paper investigates the cross-market transmission of the London Stock Exchange's reaction to the terrorist attacks of 2005. It focuses on how this reaction was transmitted to two other major European stock exchanges: Frankfurt and Paris. To this effect, high frequency data are used and multivariate GARCH models are employed. Findings reported herein indicate that the volatility of stock market returns is increased in all three cases.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: H56; G1; G15; 330; terrorism; capital markets; contagion; multivariate GARCH